Analysis of The Impact Of NIM, LDR and NPL on Bank Profitability with Variable Mediating Firm Size (Empirical Study on Public Banks Listed on IDX in 2015-2019) - Widyakto, Adhi; Suhardjo, Yohanes; Prapti NSS, RR Lulus; Ardiansari, Anindya (Management Analysis Journal, 2021)
The reason of this think about to impact of NIM, LDR and NPL on the productivity of Commercial Banks Go Open with Variable Estimate control. Benefit is anticipated with ROE as a gage of the sum of benefit generated. The tests utilized in this think about were go open commercial banks recorded on IDX (IDX) amid the period 2015-2019. The number of tests utilized as numerous as 18 banks were taken by purposive inspecting strategy. The examination strategy of this ponder employments different direct relapses with spss 24 program that has already passed the classic presumption test. The comes about of this investigate appear that NIM incorporates a critical positive impact on ROE. NPL contains a noteworthy negative impact on ROE. Long remove relationship incorporates a positive but not noteworthy impact on ROE. On the other hand, the utilize of measure as a control variable appears that NIM features a critical positive impact on ROE.